Radiation sensors for medical, industrial and environmental applications: how to engage with schools and the general public. (21st November 2017) - Seitz, B; Campos Rivera, N; Gray, R; Powell, A; Thomson, F
Abstract: Radiation, radiation detection and radiation protection are topics in physics and its applications which generate a wide interest in the public. This interest is either generated through medical procedures, applications of nuclear energy or nuclear accidents. The technical nature of these topics usually means that they are not well covered in the normal education stream, opening many opportunities to engage with schools and the general public to showcase the latest developments and their applications. The detection of radiation is at the very heart of understanding radiation, its fascination and associated fears. The outreach group of the nuclear physics group at the University of Glasgow demonstrates a number of successful outreach activities centred around radiation detection and described in this paper, focusing on activities delivered to a variety of audiences and related to applied nuclear physics work within our group. These concentrate on the application of novel sensor technologies for nuclear decommissioning, medical imaging modalities and the monitoring of environmental radioactivity. The paper will provide some necessary background material as well as practical instructions for some of the activities developed.